Commodity risk assessment of Taxus baccata plants from the UK - EFSA Panel on Plant Health (PLH); Antonio Vicent Civera; Paula Baptista; Anna Berlin; Elisavet Chatzivassiliou; Jaime Cubero; Nik Cunniffe; Eduardo de laPeña; Nicolas Desneux; Francesco Di Serio; Anna Filipiak; Beata Hasiów‐Jaroszewska; et al. (EFSA Journal)
Abstract The European Commission requested the EFSA Panel on Plant Health to prepare and deliver risk assessments for commodities listed in Commission Implementing Regulation (EU) 2018/2019 as ‘High risk plants, plant products and other objects’. This Scientific Opinion covers plant health risks posed by plants of Taxus baccata imported from the United Kingdom (UK) as: (a) bundles of 2‐year‐old bare root plants (whips), (b) 2‐ to 7‐year‐old bare root plants, either exported as single plants or in bundles, (c) 2‐year‐old cell grown plants exported in bundles, and (d) 3‐ to 15‐year‐old plants in pots. The assessment was performed considering the available scientific information, including the technical information provided by the UK. All pests associated with the commodity were evaluated against specific criteria for their relevance for this opinion. One EU quarantine pest, Phytophthora ramorum (non‐EU isolates) fulfilled all relevant criteria and was selected for further evaluation. For the selected pest, the risk mitigation measures implemented in the technical dossier from the UK were evaluated taking into account the possible limiting factors. An expert judgement was given on the likelihood of pest freedom taking into consideration the risk mitigation measures acting on the pest, including uncertainties associated with the assessment. The fact that T. baccata is an evergreen plant on which P. ramorum can cause foliar infection was considered a critical element in the risk assessment. In addition, the age of the plants was considered, reasoning that older trees are more likely to be infected mainly due to longer exposure time and larger size. The degree of pest freedom slightly differs between bare root plants (including whips) and plants in pots (including cell grown plants), with plants in pots being less likely pest free. The Expert Knowledge Elicitation (EKE) indicated with 95% certainty that between 9699 and 10,000 3‐ to 15‐year‐old plants in pots and bundles of 2‐year‐old cell grown plants per 10,000 will be free from P. ramorum (non‐EU isolates).